Monitoring, Management and Topological Display Device using wireless network managed clients - Melo Torres, Oscar Javier; Barón Velandia, Julio; Daza Corredor, Alejandro Paolo (TECCIENCIA, 2013)
The technological breakthroughs and developments made both online and on mobile devices has enabled the deployment of services that can be used by users without being in a fixed physical location or require transporting equipment with high computational processing power channel , this release has allowed people greater mobility and generating new business models based on e-commerce, to ensure an adequate service level a constant monitoring action is required to detect failures and shortcomings in timely manner without implying that staff is permanently in the management center . This paper presents the methodology, development and benefits of a prototype that allows visual access and ubiquitous real-time behavioral information and status of network devices from a mobile device requiring only a Web browser that can run the HTML5 and JavaScript protocol.